Low Abundance of Plastic Fragments in the Surface Waters of the Red Sea - Martí, Elisa; Martin, Cecilia; Cózar, Andrés; Duarte, Carlos M. (Frontiers in Marine Science, 2017)
The floating plastic debris along the Arabian coast of the Red Sea was sampled by using surface-trawling plankton nets. A total of 120 sampling sites were spread out over the near-shore waters along 1,500 km of coastline during seven cruises performed during 2016 and 2017. Plastic debris, dominated by millimeter-sized pieces, was constituted mostly of fragments of rigid objects (73%) followed by pieces of films (17%), fishing lines (6%) and foam (4%). These fragments were mainly made up by polyethylene (69%) and polypropylene (21%). Fibres, likely released from synthetic textiles, were ubiquitous and abundant, although were analyzed independently due to the risk of including non-plastic fibres and airborne contamination of samples in spite of the precautions taken. The plastic concentrations (excluding possible plastic fibres) contrasts with those found in other semi-closed seas such as the neighboring Mediterranean. They were relatively low all over Red Sea (< 50,000 items km-2; mean ± SD = 3,546 ± 8,154 plastic item km-2, 1.1 ± 3.0 g km-2) showing no clear spatial relationship with the distribution of coastal population. Results suggests a low plastic waste input from land as the most plausible explanation for this relative shortage of plastic in the surface waters of the Red Sea; however, the additional intervention of particular processes of surface plastic removal by fish or the filtering activity of the extensive coral reefs along the coastline cannot be discarded. In addition, our study highlights the relevance of determining specific regional conversion rates of mismanaged plastic waste to marine debris, accounting for the role of near-shore activities (e.g. beach tourism, recreational navigation), in order to estimate plastic waste inputs into the ocean.